2022
DOI: 10.2174/18742106-v16-e2209270
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and Non-modifiable Risk Factors Affecting Oral and Periodontal Health and Quality of Life in South Asia

Abstract: Objectives: The study aimed to review the prevalence of periodontal disease and associated factors among developing South Asian countries. The review was also aimed at providing an insight into how such factors play a role in affecting the Quality of life of patients with compromised oral health. Background: It has been observed that Oral health directly correlates with the Quality of life of an individual, so it is imperative to understand this, particularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…Periodontal pathogens are widely recognized to be responsible for the onset and deterioration of the periodontal conditions, which triggers the host immune response and inflammation to protect against these pathogens [9][10][11]. In addition, risk factors for the progression to periodontal disease are poor oral hygiene, aging, male gender, diabetes, low socioeconomic status, education level, consumption of alcohol and tobacco [12].…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal pathogens are widely recognized to be responsible for the onset and deterioration of the periodontal conditions, which triggers the host immune response and inflammation to protect against these pathogens [9][10][11]. In addition, risk factors for the progression to periodontal disease are poor oral hygiene, aging, male gender, diabetes, low socioeconomic status, education level, consumption of alcohol and tobacco [12].…”
Section: Introductionmentioning
confidence: 99%
“…While the World Health Organization (WHO) guidelines on sugar intake recommend no added sugar consumption under age 2 and afterwards less than 5% of intake from free sugars, the majority of children worldwide and in LMICsparticularly in Latin America and Asia-consume added sugars earlier and in greater quantity and frequency than recommended, contributing to dental caries as well as obesity, type 2 diabetes, cardiovascular disease and cancers [57][58][59]. This suggests a critical need for healthier food environments and oral health and nutrition literacy for families [60,61]. Overall, we found that children in larger families were less likely to be cavity-free, but more likely to have had a dental visit, which we believe is consistent with our findings from a separate analysis of this sample that families primarily seek dental care for dental problems (usually dental pain due to caries) rather than for disease prevention [62].…”
Section: Discussionmentioning
confidence: 99%
“…An ideal prosthetic treatment should not only be limited in restoring function and esthetics in the patient, but also achieve a healthy relationship with the periodontal tissues [ 48 , 49 , 50 , 51 ]. Thus, there are some factors that influence periodontal health such as cervical emergence profile, periodontal phenotype, biological thickness, materials and fabrication method of the restoration, prosthetic margin location, prepared tooth finish line, cementing materials and marginal and internal fit [ 10 , 12 , 52 ].…”
Section: Periodontal Health In Patients With Fixed Dental Prosthesismentioning
confidence: 99%